UPAYA MENINGKATAN MINAT DAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN MISSOURI MATHEMATIC PROJECT SISWA KELAS X MC SMK TAMANSISWA JETIS YOGYAKARTA - Irma Rahmawati; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
The purpose of this research is to increase interest and achievement in mathematics learning models Missouri Mathematic Project (MMP) in class X MC SMK Tamansiswa Jetis Yogyakarta. This research is Classroom Action Research (CAR) conducted in two cycle. The subjects of this research is students of class X MC SMK Negeri Tamansiswa Jetis Yogyakarta totaling 23 students. Data collection techniques in this research uses observation, questionnaires, tests and documentation. The results showed after the application of models Missouri Mathematic Project (MMP), interest and learning mathematics achievement of students has increased. Mathematics achievement of students and the percentage of completeness students (with KKM 75)also increased. Models Missouri Mathematic Project (MMP) to increase interest in mathematics learning and achievement of students, it is suggested that mathematics teachers can apply the learning model.